Dual-functional lignin fuel cells: Coupling electricity generation with lignosulfonate valorization using dodecyl sulfate-intercalated NiS2 anode catalysts - Danlu, Zhang; Peng, Wang; Qiqi, Dai; Yan, Xu; Qingyou, Liang; Xu, Zeng; Chuanfu, Liu; Wu, Lan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •NiS2-SDS/NF with multilayer structure are highly reactive towards lignin oxidation.•A dual functional and stable lignosulfonate fuel cell was developed.•The lignosulfonate fuel cell attains a peak power density of 113 mW/cm2 at 50 °C.•The fuel cell converts lignosulfonate into oxalic acid during discharging. This study presents a nickel sulfide catalyst intercalated with sodium dodecyl sulfate (NiS2-SDS/NF) synthesized through hydrothermal and pyrolytic methods. The unique “cabbage-like” morphology of NiS2-SDS/NF enhances accessibility and charge transfer of active sites, confirmed by SEM, TEM, XRD, and XPS analyses. Electrochemical performance assessments reveal exceptional catalytic activity towards the oxygen evolution reaction and lignin oxidation, with NiS2-SDS/NF demonstrating the highest current density and lowest Tafel slope among the tested catalysts. The lignosulfonate direct fuel cell utilizing NiS2-SDS/NF as anode catalyst achieves a peak power density of 113 mW/cm2 at 50 °C, with stable long-term performance and energy utilization rate of 70 %. This setup also converts lignosulfonate into oxalic acid with over 23 wt% yield and high selectivity. In-situ Raman and infrared spectroscopy elucidate the oxidation mechanism, showing the formation of NiOOH active sites and the cleavage of lignin macromolecules into aromatic and aliphatic acids. This work highlights the potential of NiS2-SDS/NF for efficient lignin valorization and sustainable energy production, paving the way for future optimization and application of lignin-based fuel cells.